Sonic the hedgehog (2018), volume 16 ebook Misadventures. - Flynn, Ian (Sonic the Hedgehog (2018), 2024)
While the villains are away, the heroes will play! Sonic and his pals go off on their own adventures, even as all roads lead them back to one another. With Dr. Eggman and Surge subdued for now, Sonic and friends have a chance to relax, reset, and plan for the future. Or so they hope. If anything can be counted on around Sonic, it’s that new misadventures are just waiting to happen! To start, Amy visits Knuckles on Angel Island to return a relic. The island, as always, has a few surprises in store for them as they catch up. Meanwhile, Mimic is putting together the purrfect disguise to infiltrate the Restoration, and Silver is left to his own devices at Restoration HQ. Sonic himself has joined Blaze on a trip around the world where they will see all the sights to be seen! Collecting IDW’s Sonic the Hedgehog #62–66.